2003
DOI: 10.1172/jci200317662
|View full text |Cite
|
Sign up to set email alerts
|

CD137 costimulatory T cell receptor engagement reverses acute disease in lupus-prone NZB × NZW F1 mice

Abstract: Systemic lupus erythematosus (SLE) is a CD4+ T cell–dependent, immune complex–mediated, autoimmune disease that primarily affects women of childbearing age. Generation of high-titer affinity-matured IgG autoantibodies, specific for double-stranded DNA and other nuclear antigens, coincides with disease progression. Current forms of treatment of SLE including glucocorticosteroids are often inadequate and induce severe side effects. Immunological approaches for treating SLE in mice using anti-CD4 mAb’s or CTLA4-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
113
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 30 publications
(15 reference statements)
9
113
1
Order By: Relevance
“…Furthermore, our study shows that CD137 costimulation is not only able to down-regulate FDCs and prevent GC formation, it also can diminish FDCs and eliminate existing GC after the initiation of a humoral immune response. This is consistent with the idea that anti-CD137 treatment interferes with autoantibody production even after autoimmune disease establishment (26,27). Similarly, 2A treatment can abolish the formation of FDC networks in Fasdeficient mice in the absence of exogenous Ags, followed by a diminished production of autoantibodies (data not shown).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, our study shows that CD137 costimulation is not only able to down-regulate FDCs and prevent GC formation, it also can diminish FDCs and eliminate existing GC after the initiation of a humoral immune response. This is consistent with the idea that anti-CD137 treatment interferes with autoantibody production even after autoimmune disease establishment (26,27). Similarly, 2A treatment can abolish the formation of FDC networks in Fasdeficient mice in the absence of exogenous Ags, followed by a diminished production of autoantibodies (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…Agonistic mAbs against CD137 have been shown to be effective in promoting T cell-mediated immune responses in vivo (22)(23)(24), but they paradoxically also inhibit Tdependent humoral immunity (25) and prevent autoantibody production in various autoimmune disease models (26 -28). Previous studies attributed CD137-mediated suppression of Tdependent Ab responses to the inhibition of Th cells due to the induction of their anergy, activation-induced cell death, or induction of CD11c ϩ CD8 ϩ suppressor T cells and to the depletion of B cells (25)(26)(27)(28). Our current study unexpectedly found that CD137 costimulation dramatically down-regulates FDC networks in a T cell-dependent manner.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…It has been described that the agonistic anti-CD137 antibodies in vivo have a preferential role as a costimulation molecule for CD8 + T cells, with no detectable effect on CD4 + T cells [34][35][36]51]. Moreover, some experiments have suggested that CD137 stimulation might induce CD4 + T cell anergy [52,53] or activationinduced T cell death [54]. However, there are several reports in in vitro models supporting the costimulatory effect of CD137 on CD4 + T cell proliferation and survival activation.…”
Section: Discussionmentioning
confidence: 99%